Primordial dark matter halos from fifth forces - Savastano, Stefano; Amendola, Luca; Wetterich, Christof (Physical review, 2019)
We argue that primordial dark matter halos could be generated during radiation domination by long-range attractive forces stronger than gravity. In this paper, we derive the conditions under which these structures could dominate the dark matter content of the Universe while passing microlensing constraints and cosmic microwave background energy injection bounds. The dark matter particles would be clumped in objects in the solar mass range with typical sizes of the order of the solar system. Consequences for direct dark matter searches are important.
Gesehen am 11.12.2019